Analisis Pemahaman laporan Keuangan pada UMKM di Kecamatan Medan Marelan - Budi Dharrma; Habib Lauda Nararya; Rediansyah Saranan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The research method used in this study is a qualitative research method. The object review is used as a reference and obtains findings of facts and strengthens research results. The object review used in this study uses previous research that has relevance to the understanding of financial statements in the Convection Sector in Medan Marelan District. The reason for choosing this research object is due to general knowledge whether one of the business actors in Medan Marelan District understands financial reports or not. So that the writer can find out the factors that drive the business whether they have to know the financial statements well.